ANALISIS TOLERANSI BERAGAMA ANTAR SISWA DI SMA NEGERI 1 BEDUAI - Sucinda, Juniardi; Bahari, Yohanes; Sulistyarini, Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research is "The Analysis of Inter-Religious Tolerance in SMA Negeri 1 Beduai". The purposes of this study are to describe (1) Religious tolerance in the form of respecting other religions among students in SMA Negeri 1 Beduai. (2) Tolerance in the form of religious freedom among students in SMA Negeri 1 Beduai. The method which used in this research is qualitative method with descriptive analysis. The tools of data collection are observation checklist, interview and documentation. The results showed that (1) Religious tolerance in the form of respecting other religions among students in SMA Negeri 1 Beduai is very good. This is evidenced by the mutual respect of colleagues in different religions in this school, harmonious relationship of friendship and the absence of conflict which coming from religion matters. (2) In the case of religious freedom, students in SMA Negeri 1 Beduai are free to carry out religious activities without fear. They are free to wear religious attributes and never get forced to practice religion outside their belief.Â Keywords: Religious Tolerance, Respect, freedom of religion